Off-line Programming of Robotized Filament Winding and Its Application - XU Jia-zhong; SUN Dong; YANG Hai; LIU Mei-jun (Journal of Harbin University of Science and Technology)
In this paper，we make a research on mesh post disposal of composite winding and robot motion control theory and establish an off-line wind programming and simulation platform of an industrial robot based on Matlab and ADAMS. It can do CAD of winding path according to equal distance，equal height and equal fiber length three different envelop forms，and generate the executable file on the robot automatically. At the same time， it can optimize the winding path by doing animation simulation and motion analysis of the winding process. Simulation and physical experiments of winding one bent pipe have been done. It shows that the platform is reliable and practical，winding path design is convenient and accurate and the simulation effect is ideal. Simulated experiment can effectively shorten robot winding path development，cut down the times of physical experiments and save the development costs.